It is not mine. Surrogacy between Natural Body and Artificial Body - Viviani, Debora (Italian Sociological Review, 2017)
Drawing on Jean Baudrillard’s approach and his process of simulation, which is a useful key for interpreting and analysing the natural body-artificial body dichotomy, this article aims to raise questions about the repercussions that the new culture of the body and the practices associated with the medicalization of maternity have on the construction of personal and social identity. The debate encompasses issues in the realm of bioethics, the presence or absence of human rights, contractual exchange, the processes of commodification of the body, women and pregnancy, and processes that manipulate human life. The scope of the observations thus extends to subjects such as bioethics, body ownership and the manipulation of life, to the point of questioning the construction of gender identity and even the very concept of mother. The objective of this study is to render the complexity of the issue of surrogacy and highlight the resulting theoretical challenges faced by the social sciences. It is still essentially exploratory in nature and is intended as a starting point for the development of this research topic, raising certain questions in an attempt to provide the sociological debate with new theoretical and empirical challenges.